Modeling residence time and effluent dispersal in a mariculture area - Magdaong, Evangeline T. (Marine Science Institute, College of Science, University of the Philippines Diliman, 2008)
Numerical hydrodynamic, residence time and waste dispersal models were developed to determine the siting criteria and fish pen spacing in milkfish culture. Residence time was used as a basis for aquaculture site selection. Field measurements revealed significant flow reduction with presence of fish farm. The effect of fishery structures on residence time was represented as enhanced frictional drag in the model to determine sedimentation footprint of cages and pens. Simulation results showed straits or passages are vulnerable to the presence of fish farm.